Analisis Spasial Permukiman Transmigran Dan Sarana Pelayanan Di Kecamatan Timpeh Kabupaten Dharmasraya - Fitroh, Nurul; Elvi Zuriyani (Universitas Pendidikan Ganesha, 2023)
This research is motivated by factors to analyze transmigrant settlements and service facilities in the Timpeh Subdistrict, Dharmasraya Regency using a geographic information system. The results of the research are expected to explain how transmigrant settlements and service facilities in the Timpeh Subdistrict, Dharmasraya Regency. The type of research used in this research is spatial descriptive. The population in this study is the area where there are migrant communities in Timpeh Subdistrict, Dharmasraya Regency, West Sumatra Province. In this study using total sampling with a sample of all areas where there are transmigrant people in Timpeh Subdistrict, Dharmasraya Regency, West Sumatra Province. Based on the results of the study, it can be concluded that first, the distribution of transmigrant settlements in Timpeh Subdistrict is uneven and different. There are 4 villages with different numbers of settlements in each village. In Nagari Panyubarangan there are 7 settlements, Nagari Ranah Palabi with 8 settlements, Nagari Tabek with 8 settlements, Nagari Taratak Tinggi with 12 settlements. Second, education and health service facilities in Timpeh Subdistrict, Dharmasraya Regency are unevenly distributed in each Nagari. The distribution of educational facilities in this Subdistrict with a total of 15 schools and health service facilities has 7 main health centres and auxiliary health centres (Pustu). Third, Nagari Taratak Tinggi there are 6 educational service facilities and 2 health service facilities that can be reached by transmigrant settlement communities, Nagari Tabek has 4 educational service facilities and 2 health service facilities that can be reached by transmigrant settlement communities. Nagari Ranah Palabi has 5 educational service facilities and 2 health service facilities that can be reached by transmigrant settlement communities, but the Nagari in Panyubarangan has 2 educational service facilities that can be reached by transmigrant residential communities and does not have health service facility coverage areas.